Audiovisual Cues and Perceptual Learning of Spectrally Distorted Speech. - Pilling, Michael; Thomas, Sharon (Language & Speech, 2011)
Two experiments investigate the effectiveness of audiovisual (AV) speech cues (cues derived from both seeing and hearing a talker speak) in facilitating perceptual learning of spectrally distorted speech. Speech was distorted through an eight channel noise-vocoder which shifted the spectral envelope of the speech signal to simulate the properties of a cochlear implant with a 6 mm place mismatch. Experiment 1 found that participants showed significantly greater improvement in perceiving noise-vocoded speech when training gave AV cues than when it gave auditory cues alone. Experiment 2 compared training with AV cues with training which gave written feedback. These two methods did not significantly differ in the pattern of training they produced. Suggestions are made about the types of circumstances in which the two training methods might be found to differ in facilitating auditory perceptual learning of speech.